Comparison of web service architecture based on architecture quality properties - Wu, Chen; Chang, Elizabeth (IEEE, 2005)
Web service research has been focused on the issues of automatic binding, performance, scalability, and security, however, little research has been done in evaluation of web service architectures, namely Broker based. Examples of these are Matchmaker Broker, Layered Matchmaker, Facilitator, Layered facilitator, and Peer to peer (P2P) based, such as P2P Discovery, Match Maker and P2P, Split Code and P2P execution, Mobile Code with P2P etc. Another consideration is its impact on the adoption in distributed Internet environment. In this paper we introduce a methodology for measuring and evaluating web service architecture style, and we present our development of a set of architectural quality properties, and use these quality properties to carry out comparison and contract of current web services architectures. We provide a detailed analysis and critique of these, and these could be served as a guidelines for the next generation of web services development, which could adopted into the distributed environment.